The impact and cost-effectiveness of pneumococcal immunisation strategies for the elderly in England - Danelian, G; Burton, L; Bayley, T; Sanchez-Marroquin, A; Park, J; Manley, H; Choi, Y; Andrews, N; Ladhani, S; Earnshaw, A; Gritzfeld, JF; Trotter, C; et al. (Elsevier, 2024)
Pneumococcal disease, presenting as invasive pneumococcal disease (IPD) or community-acquired pneumonia (CAP) is an important cause of illness and hospitalisation in the elderly. To reduce pneumococcal burden, since 2003, 65-year-olds in England have been offered a 23-valent pneumococcal polysaccharide vaccine (PPV23). This study compares the impact and cost-effectiveness (CE) of vaccination with the existing PPV23 vaccine to the new 15-and 20-valent pneumococcal conjugate vaccines (PCV15 and PCV20), targeting adults aged 65 or 75 years old. We developed a static Markov model for immunisation against pneumococcal disease, capturing different vaccine effectiveness and immunity waning assumptions, projecting the number of IPD/CAP cases averted over the thirty years following vaccination. Using an economic model and probabilistic sensitivity analysis we evaluated the CE of the different immunisation strategies at current vaccine list prices and the willingness-to-pay at a median threshold of £20,000/QALY and an uncertainty threshold of 90% of simulations below £30,000/QALY. PCV20 averted more IPD and CAP cases than PCV15 or PPV23 over the thirty years following vaccination: 353(360), 145(159) and 150(174) IPD and 581(673), 259(485) and 212(235) CAP cases at a vaccination age of 65(75) under base vaccine effectiveness assumptions. At the listed prices of PCV20 and PPV23 vaccines as of May 2023, both vaccines were cost-effective when vaccinating 65- or 75-year-olds with an ICER threshold of £20,000 per QALY. To achieve the same cost-effectiveness as PPV23, the additional cost of PCV20 should be less than £44(£91) at an ICER threshold of £20,000/QALY (£30,000/QALY) if vaccination age is 65 (or £54(£103) if vaccination age is increased to 75). We showed that both PPV23 and PCV20 were likely to be cost-effective. PCV20 was likely to avert more cases of pneumococcal disease in elderly adults in England than the current PPV23 vaccine, given input assumptions of a higher vaccine effectiveness and slower waning for PCV20.